Can Looking at a Hand Make Your Skin Crawl? Peering into the Uncanny Valley for Hands. (September 2013) - Poliakoff, Ellen; Beach, Natalie; Best, Rebecca; Howard, Toby; Gowen, Emma
It is postulated that there is an uncanny valley, whereby human-like stimuli such as robots or animated characters that fall short of being fully human are perceived as eerie or unsettling. Previous research has explored the existence of this effect for faces and whole bodies, while here we explore responses to photographs of real and artificial hands. In keeping with the notion of an uncanny valley, prosthetic hands that were of intermediate human-likeness were given the highest ratings of eeriness. However, within the categories of hands, ratings of eeriness reduced as human-likeness increased, suggesting a more complex pattern. Further investigation of this effect will be of relevance to the design of prosthetic limbs and could be used to test theories of the uncanny valley and social perception with simple stimuli.